(untitled) (Al-Qamar, 2025)
This study explores the prevalence, causes, and socio-cultural dynamics of gender-based violence (GBV) in Pakistani society, with a particular focus on District Multan. Using a mixed-method approach, data were collected from diverse demographic groups through surveys, interviews, and focus group discussions. The research examines the patterns of physical, emotional, economic, and psychological abuse, identifying key factors such as patriarchal norms, lack of legal awareness, poverty, and insufficient institutional support systems. Findings indicate that GBV in Multan is deeply rooted in traditional gender roles, socio-economic inequalities, and cultural perceptions that normalize violence against women. The study also highlights the challenges faced by victims in accessing justice, including fear of social stigma, inadequate law enforcement, and weak implementation of protective legislation. Recommendations include community-based awareness campaigns, gender-sensitive training for law enforcement agencies, strengthening legal protections, and promoting women’s empowerment initiatives. This research aims to contribute to the academic discourse on GBV in Pakistan and provide practical insights for policymakers, NGOs, and community leaders to develop effective intervention strategies.